54‐3: Invited Paper: Flexible Active‐Matrix OLET Display on a Plastic Substrate. Issue 1 (May 2016) - Hsieh, Hsing‐Hung; Chen, Wei‐Chung; Generali, Gianluca; Soldano, Caterina; D'Alpaos, Riccardo; Turatti, Guido; Biondo, Viviana; Muccini, Michele; Huitema, Edzer; Facchetti, Antonio
Abstract : The organic light‐emitting transistors (OLETs) with a novel tri‐layer organic semiconducting heterostructure architecture and good performance, including record high EQE, is presented. In addition, an active‐matrix display based on OLETs, without driving TFTs, will be demonstrated on a plastic substrate. The potential advantages of such technologies will be discussed.